Oxidative and Inflammatory Parameters in Children and Adolescents With ADHD. - Koç, Sümeyye; Güler, Eray Metin; Derin, Songül; Gültekin, Fatih; Aktaş, Selman (My University, 2023)
This study aims that oxidative stress and inflammation status in children and adolescents with attention deficit hyperactivity disorder (ADHD) compared to their healthy peers.

Thirty ADHD and healthy controls were included in this study. ADHD diagnosis according to the DSM-V and Conners' teacher and parent rating scale by a structured psychiatric interview. Total oxidant status (TOS), total antioxidant status (TAS), and total and native thiol levels were determined using photometric methods. Presepsin, Interleukin (IL) 1-ß, IL-6, and Tumor Necrosis Factor-alpha (TNF-α) levels were measured with commercial ELISA kits.

We showed that TOS and oxidative stress index were significantly higher in the ADHD group, and TAS was lower than in the control group (<.001). Similarly, IL1-ß, IL-6, and TNF-α levels were statistically higher in the ADHD group. Backward LR regression analysis reveals that TOS and IL-6 predicted ADHD.

TOS and IL-6 levels may play a role in the pathogenesis of ADHD.
Keywords: IL-6; antioxidant; attention deficit hyperactivity disorder; inflammation; oxidative stress